Association between emotional regulation and family support with quality of life of women with cervical cancer - Putu Noviana Sagitarini; Putu Cintya Denny Yuliyatni; Ni Made Swasti Wulanyani (Universitas Udayana, 2019)
Background and purpose: Cervical cancer ranks third globally and ranks second in Indonesia for all cancers in women. Women with cervical cancer experience physical and psychological disorders that can affect their quality of life. This study aims to determine the association between emotional regulation and family support with the quality of life of women with cervical cancer. Methods: A cross sectional survey was conducted in April 2018 at the Sanglah Hospital Obstetric Clinic. The study samples were chosen consecutively and consisted of 100 women with cervical cancer who underwent outpatient care. Data was collected using questionnaires filled in by the respondents and from the patient's medical records. Bivariate analysis was conducted with chi square test and multivariate with logistic regression. Results: The results showed that emotional regulation and family support were found to be significantly related to the quality of life of women with cervical cancer, each with AOR=17.64; 95%CI: 3.01-103.46; p=0.001 and AOR=11.28; 95%CI: 1.88-67.78; p=0.008. Conclusion: Emotional regulation and family support are related to the quality of life of women with cervical cancer. Efforts to improve emotional regulation and family support for patients should be carried out to improve their quality of life.